Relationship between the single nucleotide polymorphism rs4704963 (T> C) of the Early B-Cell Factor 1 gene and smoking in a population with risk factors for coronary heart disease with and without acute coronary syndromes treated in Buenos Aires City, Argentina - Carbajales, Justo (2019)
Introduction: Early B-cell factor 1 (EBF1) gene participates in the development of the central nervous system and is expressed in adipocytesand olfactory neuroepithelium, which is intimately linked with the emotion and reward system in adults. For this reason, it could be linkedto tobacco addictionObjective: The aim of this study was to determine probable association between the EBF1 gene rs4704963 SNP (T>C) with smoking habitsin a population of patients with multiple coronary risk factors (CRF) with and without acute coronary syndromes (ACS).Materials and methods: Between December 2015 and March 2017, 104 consecutive patients with two or more risk factors, with or withoutACS were included. A 10-mL blood sample was collected from all the patients for SNP determination. DNA genotyping was carried out usingthe nested PCR technique and subsequent sequencing.Results: Mean age was 59.1 ± 9.17 years and 59.6% were men. The most common CRF were smoking habits (60.6%) hypertension (56.7%)and diabetes (48.1%).None of the patients had the homozygous T / T haplotype while 17 patients (16.3%) presented the T / C haplotype forheterozygous SNP. Among the 17 patients with the SNP detected, 16 (94.1%) were smokers compared to 54% of smokers in those patientswithout the SNP detected (p = 0.002).In those patients with ACS and smoking habits, the SNP was detected in 21.3% versus 0% in those with ACS and no history of smoking habits(p= 0.029)Conclusion: A significant association was observed between the EBF1 gene rs4704963 SNP (T> C) with smoking habits in patients with ACSand in those with CRF without ACS. Further research including more patients is necessary to confirm these findings in order to customizedecision-making to prevent this addiction and indicate the appropriate treatment when smoking is present.